Sentencing contempt of court in international criminal justice: an unforeseen problem concerning sentencing and penalties - D'Ascoli, Silvia (Journal of international criminal justice, 2010)
International criminal tribunals, like any criminal court, have been faced with offences against the administration of justice, such as contempt of court. The power of the UN ad hoc Tribunals to punish these offences has raised problematic issues mainly concerning respect for the principle of legality (including frequent amendments to contempt-provisions, and the substantial increase of the sentencing frame for contempt within only a few years). This article seeks to clarify some aspects concerning applicable penalties and sentencing for contempt of court through the examination of the case law of the ad hoc Tribunals and the Special Court for Sierra Leone, discussing its implications for the principle of legality. It is argued that the process followed in sentencing contempt is in many aspects not dissimilar to the traditional judicial practice of the Tribunals concerning purposes of punishment, aggravating and mitigating circumstances and guilty pleas